EFFECT OF SOME CYCLIC UREA COMPOUNDS ON PLANT REGENERATION OF BACOPA MONNIERI (L.) PENNELLE - SUSHMA KUMARI; ANIL SINDHU; ASHOK K ROHILLA; ANIL K POONIA; J.S. RANA (International Journal of Pharma and Bio Sciences, 2014)
This paper highlights the study of effects of various urea derived herbicides viz., monuron, diuron, thidiazuron and classical cytokinin i.e., BAP on shoot morphogenetic behaviour of medicinal plant Bacopa monnieri. The studies were carried out on different cultivars. Thidiazuron (0.02µM) induced highest shoot morphogenetic response from axillary buds of Chuharpur cultivar with a maximum number of 13.36 shoots per explant followed by 8.33 and 5.55 in Lucknow and Hisar cultivar. Diuron(0.10 µM) showed shoot morphogenesis highest in Chuharpur cultivar 11.20 per explant. Monuron (0.10 µM) also showed 11.53 in Chuharpur cultivar. Also, the shoot regeneration response of shoot tip explant found to be high with a mean no. of 9.17 shoots per explant with Thidiazuron(0.02µM) . For rooting, different concentrations of NAA, IBA and IAA were used and highest rooting was observed on MS medium supplemented with NAA(1.5mg/l)+IBA(1.5mg/l) with 96% response. The in vitro regenerated plantlets were transferred to greenhouse for hardening. The soil mixture having sand:soil:vermicompost (1:1:1) showed the best response in terms of 97% survival rate. Results of the present study supports the potential of thidiazuron and monuron in exerting unusual cytokinin like activity that are useful for micropropagation of endangered medicinal plants.